Analisis Profesionalisme Dan Komitmen Sebagai Fresh Graduate Pada Kantor Jasa Akuntansi PT. Eriadi Fatkhur Rokhman - Syahri Ramadhan; Aqwa Naser Daulay (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to analyze the levels of professionalism and commitment among fresh graduates working at the Accounting Services Office of PT. Eriadi Fatkhur Rokhman. Fresh graduates represent a relatively new workforce in the industry, making it essential to understand the extent of their grasp of professionalism and their commitment to the company they are employed in. The research employed interview methods to gather data from the Manager Operational working at the accounting services office. The collected data were subjected to various statistical and qualitative analysis tools to evaluate their levels of professionalism and commitment. The results of this research indicate that a significant majority of fresh graduates at the Accounting Services Office of PT. Eriadi Fatkhur Rokhman have exhibited commendable levels of professionalism, possessing a strong understanding of workplace ethics and accountant professional standards. They have also demonstrated a high level of commitment to the company and their jobs. However, the research has also identified several factors influencing the levels of professionalism and commitment among fresh graduates, such as management support, training, and career development. Hence, recommendations are provided to enhance the professionalism and commitment of fresh graduates, including more intensive training programs, stronger management support, and clearer career development opportunities. This research provides valuable insights into the significance of professionalism and commitment in the workplace, particularly for fresh graduates in the accounting services industry. The research findings can serve as guidance for companies to improve human resource development and ensure that fresh graduates become valuable assets within the organization.